1983
DOI: 10.1056/nejm198303103081002
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Muscle Protein Degradation and Prostaglandin E2Release by Leukocytic Pyrogen (Interleukin-1)

Abstract: To clarify the mechanisms underlying the loss of body protein during fever and sepsis, we incubated rat muscles with highly purified human leukocytic pyrogen. This polypeptide, which appears identical to interleukin-1, is released by leukocytes and signals the onset of fever in the hypothalamus. In muscles incubated at 37 degrees C, leukocytic pyrogen stimulated net protein degradation by 62 to 118 per cent (P less than 0.001). Proteolysis increased, but rates of muscle-protein synthesis did not change. The py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
222
6
8

Year Published

1985
1985
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 661 publications
(242 citation statements)
references
References 32 publications
6
222
6
8
Order By: Relevance
“…Recent studies have revealed that mobilisation of amino acids from skeletal muscle tissue of patients undergoing infectious illness, trauma or sepsis is mediated by a hormone-like protein called proteolysis-inducing factor (PIF) (Clowes et al, 1983). This protein secreted by activated monocytes may be IL-1 or a IL-i-like peptide (Baracos et al, 1983;Dinarello et al, 1984). It has also been shown that prostaglandin E2 production was increased by these macrophage secretory products and an inhibitor of the cycloocygenase pathway, indomethacin, partially attenuated the stimulation in skeletal muscle protein degradation (Baracos et al, 1983 (Moldawer et al, 1987;Goldberg et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have revealed that mobilisation of amino acids from skeletal muscle tissue of patients undergoing infectious illness, trauma or sepsis is mediated by a hormone-like protein called proteolysis-inducing factor (PIF) (Clowes et al, 1983). This protein secreted by activated monocytes may be IL-1 or a IL-i-like peptide (Baracos et al, 1983;Dinarello et al, 1984). It has also been shown that prostaglandin E2 production was increased by these macrophage secretory products and an inhibitor of the cycloocygenase pathway, indomethacin, partially attenuated the stimulation in skeletal muscle protein degradation (Baracos et al, 1983 (Moldawer et al, 1987;Goldberg et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This protein secreted by activated monocytes may be IL-1 or a IL-i-like peptide (Baracos et al, 1983;Dinarello et al, 1984). It has also been shown that prostaglandin E2 production was increased by these macrophage secretory products and an inhibitor of the cycloocygenase pathway, indomethacin, partially attenuated the stimulation in skeletal muscle protein degradation (Baracos et al, 1983 (Moldawer et al, 1987;Goldberg et al, 1988). Likewise, the involvement of TNF-a on catabolism of proteins has been demonstrated by some studies in vivo (Warren et al, 1987;Flores et al, 1989;Fong et al, 1989) and in vitro Charters & Grimble, 1989) and refuted in others (Kettelhutt & Goldberg, 1988;Moldawer et al, 1987;Rofe et al, 1987;Michie et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the immune system leads to production of in¯ammatory cytokines such as interleukin-1b (IL-1), tumor necrosis factor (TNF), and interleukin-6 (IL-6), which can cause amino acid export from muscle (Baracos et al, 1983;Clowes et al, 1983;Tsujinaka et al, 1996). Such a situation has been clearly demonstrated for acute illness and for chronic in¯ammatory conditions such as rheumatoid arthritis and HIV infection (Roubenoff et al, 1994).…”
Section: Humoral Factorsmentioning
confidence: 99%
“…At the cellular level, IL-1 promotes the breakdown of muscle protein into amino acids (Baracos, Rodemann, Dinarello, & Goldberg, 1983), a process that is responsible for the muscle soreness experienced during infection. IL-1 also increases the availability of glucose for metabolism by peripheral tissues and the release of fatty acids from fat stores for similar use.…”
Section: Energy Demand and Balancementioning
confidence: 99%